Case reportSaphenous vein graft marker and coronary artery bypass graft stenosis in a patient 19 years after coronary artery bypass surgery - Ugurlucan, Murat; Tansel, Turkan; Umman, Sabahattin; Erzengin, Faruk; Calay, Mehmet R.; Onursal, Ertan (Archives of Medical Science, 2007)
The saphenous vein is one of the most commonly used conduits during coronary artery bypass grafting. Saphenous vein graft markers have been introduced to facilitate coronary angiography procedures in the follow-up of patients with ischaemic heart disease. However, today these markers have only a historical aspect. This report presents a 61-year-old patient who had undergone coronary artery bypass grafting 19 years ago. A saphenous vein graft marker had been used during the operation, and there was stenosis formation at the patent vein graft coincidentally where the graft overlapped the marker.